Comparing Performance and Energy Consumption of Android Applications: Native Versus Web Approaches - Kurtz, Kellerson; Noguez, Marcelo; Zanini, Felipe; Ferreira, Paulo R.; Brisolara, Lisane (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2017)
Mobile applications are usually developed in a native way, using languages and APIs specific for a given platform, hindering the portability. As an alternative, web technologies as JavaScript and PHP have been employed enabling a same implementation to be executed in different mobile platforms without any recompilation or recoding process. This paper compares the efficiency of Android applications developed in Java (native), in PHP, in JavaScript and using Node.js through experiments that evaluate execution time and energy consumption. Our experiments explore computation complexity and as well as communication aspects relevant for the PHP and Node.js approaches. Results indicate that native implementation is the best one, regarding performance and energy consumption until a certain processing load. As this load is significantly increased, the Node.js implementation presents the lowest execution times and energy consumption.